IEEE 1451-based multi-interface module (I2M) for industrial processes automation - Batista, Edson A. [UNESP]; Silva, Alexandre C. R. [UNESP]; Gonda, Luciano; Pereira, Mauro C. [UNESP]; da Silva, Isaias; Ferreira, Wanderlei M.; D'Elia, Fabio (IEEE, 2008)
This paper describes the implementation of a multi-interface module (I2M) for automation of industrial processes, based on the IEEE1451 standard. Process automation with I2M can communicate through either wires or using wireless communication, without any hardware or software changes. We used FPGA resources to implement the I2M functions FPGA, with a NIOS II processor and ZigBee communication system (IEEE802.15), as well as RS232 serial standard. Part of the project was done in the SOPC Builder environment, which gave the designer flexibility and speed to implement the NIOS II-based microprocessor system. To test the I2M implementation, a didactic Industrial Hydraulic Module (MHI-01) was used to simulate two industrial processes to be controlled by the system proposed.
Keywords: FPGA; NIOS; RS232; SOPC; ZigBee